Nutrition and the elite and highly trained junior and young adult tennis player: A scoping review - Fleming, J. A.; Naughton, R. J.; Harper, L. D. (International Journal of Sports Science & Coaching, 2022)
Objectives The primary objective of this scoping review was to examine existing evidence regarding the dietary intake and nutrition habits of elite and highly trained junior and young adult tennis players.